A black phosphorus zirconium-doped titanium suboxide electrode for removing perfluorinated pollutants and a preparation method thereof
Patent Information
- Application Number
- CN202611408236.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-11
- Publication Date
- 2026-10-16
AI Technical Summary
[0006]本发明的目的是提供一种去除全氟污染物的黑磷掺锆亚氧化钛电极及制备方法,以解决现有改性亚氧化钛电极普遍存在的缺陷位点不稳定、活性组分分散均匀性差、复合界面结合松散、黑磷材料易氧化失活,以及对水体微量PFOS污染物选择性捕获能力弱、碳氟键矿化降解不彻底、长期电解运行稳定性不足等技术问题
(1)本发明所采用的制备工艺简洁可控、重复性强,全程采用绿色低毒溶剂体系,无需复杂精密设备与严苛反应条件,分段式制备流程操作便捷、适配规模化加工生产,产业化适配性优异。
Smart Images

Figure CN122916294A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the fields of electrochemical catalytic electrode materials and treatment of recalcitrant organic wastewater, and in particular to a black phosphorus zirconium-doped titanium suboxide electrode for removing perfluorinated pollutants and its preparation method. Background Technology
[0002] Perfluorooctane sulfonic acid (PFOS), a typical persistent perfluorinated organic pollutant, is widely used in industrial production, surface treatment, and fire-fighting materials due to its excellent chemical stability. This results in large amounts of PFOS residues accumulating continuously in various aquatic environments. The strong carbon-fluorine bonds in the PFOS molecule give it extremely strong resistance to acids, alkalis, oxidation, and heat. It is almost impossible for it to decompose spontaneously under natural conditions, exhibiting characteristics of wide migration range, high degradation difficulty, and long retention period. At the same time, PFOS has high biotoxicity and cumulative effects, easily entering the ecological cycle through water infiltration and food chain accumulation, causing continuous harm to aquatic organism reproduction and human organ metabolism. It has now been included in the category of persistent organic pollutants under key water environment control. While conventional water treatment technologies such as physical adsorption, biological decomposition, and traditional chemical oxidation can remove PFOS from water to some extent, they can only achieve phase transfer or partial chain breakage of pollutants. They are difficult to completely defluorinate and mineralize, and generally suffer from defects such as incomplete treatment, high risk of secondary pollution, and inability to adapt to the treatment of low-concentration trace pollution. They are also difficult to meet the stringent standards of refined and in-depth water environment treatment at present.
[0003] Electrochemical advanced oxidation technology, with its unique advantages of controllable reaction, no external reagents required, and thorough degradation, has become the core technology direction for the in-depth treatment of PFOS. The structural characteristics and catalytic performance of electrode materials are the key factors determining degradation efficiency. Titanium suboxide electrodes, with their advantages of high conductivity, wide electrochemical window, and strong corrosion resistance, are ideal electrode substrates for treating recalcitrant organic wastewater.
[0004] Current research on the modification of titanium suboxide electrodes mainly focuses on conventional transition metal single-doped systems. The modification methods are relatively simple, only able to increase surface active sites, and cannot effectively control electrode lattice defects and interfacial electron transport structure. Traditional modified electrodes generally suffer from uneven distribution of active components, lack of selective enrichment of pollutants, and weak interfacial bonding strength. During long-term electrolysis operation, active sites are prone to passivation, detachment, and deactivation. Especially for trace PFOS pollutants in water, they have shortcomings such as weak capture capacity, low fluoride removal efficiency, and incomplete mineralization, which seriously restricts the engineering application of titanium suboxide electrodes in the field of perfluorinated pollutant treatment.
[0005] To address the shortcomings of existing technologies, a novel modified titanium suboxide electrode was developed that combines selective enrichment, efficient polarization defluorination, and long-term stable operation. This has significant practical application value for overcoming the technical bottleneck of deep PFOS degradation and improving the treatment efficiency of perfluorinated wastewater. Summary of the Invention
[0006] The purpose of this invention is to provide a black phosphorus zirconium-doped titanium suboxide electrode for removing perfluorinated pollutants and its preparation method, so as to solve the technical problems commonly found in existing modified titanium suboxide electrodes, such as unstable defect sites, poor uniformity of active component dispersion, loose composite interface bonding, easy oxidation and deactivation of black phosphorus materials, weak selective capture ability of trace PFOS pollutants in water, incomplete mineralization and degradation of carbon-fluorine bonds, and insufficient stability during long-term electrolysis operation.
[0007] To achieve the above objectives, the present invention provides a method for preparing a black phosphorus zirconium-doped titanium suboxide electrode for removing perfluorinated contaminants, comprising the following steps: S1. Titanium plate substrate pretreatment: High-purity titanium plates are treated with organic solvents combined with ultrasonic cleaning and drying to remove surface oil and oxidation impurities and obtain a clean titanium plate substrate. S2. Preparation of zirconium-modified precursor sol: Zirconium oxychloride single precursor is incorporated into a titanium-based alcoholysis system, and after thorough stirring and sealed aging, zirconium-modified precursor sol is obtained. S3. Preparation of oxygen-vacancy-rich zirconium-modified sub-titanium oxide substrate: The zirconium-modified precursor sol obtained in S2 is uniformly coated on the surface of the titanium plate substrate obtained in S1, and processed by a segmented gradient oxygen-controlled sintering process under a nitrogen atmosphere to obtain a zirconium-modified sub-titanium oxide substrate electrode rich in stable oxygen vacancy defects. S4. In-situ bonding and passivation: Prepare a black phosphorus ethanol dispersion, immerse the zirconium-modified titanium suboxide substrate electrode prepared in S3 into the black phosphorus ethanol dispersion, and perform ice-water bath treatment. Then, construct the Zr-OP covalent bonding interface by vacuum eutectic solidification. Finally, passivate the electrode with inert light-shielding to obtain the black phosphorus zirconium-doped titanium suboxide electrode.
[0008] Preferably, the specific operation of S1 is as follows: the high-purity titanium plate is ultrasonically cleaned with acetone, anhydrous ethanol and ultrapure water for 10-15 minutes respectively, and then dried in an oven at 60-80℃ to thoroughly remove impurities and oxide films attached to the surface of the titanium plate substrate, ensuring that the subsequent sol coating adheres evenly and firmly.
[0009] Preferably, in S2, the titanium-based alcoholysis system consists of a titanium source, a chelating agent, and a solvent. The titanium source is tetrabutyl titanate, the chelating agent is glacial acetic acid, and the solvent is anhydrous ethanol. The zirconium element in zirconium oxychloride has a doping mass fraction of 1-3% in the black phosphorus zirconium-doped titanium suboxide electrode. The stirring time is 40-60 min, and the sealed aging time is 12-24 h.
[0010] Single zirconium source doping can avoid interference from multiple metal components, and chelation aging treatment can achieve atomic-level uniform dispersion of zirconium ions in the titanium oxide polymer network, eliminating the phenomenon of local agglomeration of active components.
[0011] Preferably, in S2, the mass ratio of titanium source, chelating agent, and solvent is 1:(1-3):5.
[0012] Preferably, in S3, the segmented gradient oxygen-controlled sintering process is as follows: high-purity nitrogen gas is continuously introduced for protection, the temperature is first raised to 350-380℃ at 3-5℃ / min and held for 25-35min to remove the solvent, then the temperature is raised to 820-860℃ at 3-4℃ / min and sintered at a constant temperature for 2-3h, and then naturally cooled with the furnace to lock in the high-density stable oxygen vacancy defects in the substrate.
[0013] The gradient sintering mode can effectively avoid the problems of lattice collapse, defect annihilation and grain coarsening caused by traditional high-temperature sintering, and retain high-density stable oxygen vacancy defects to the greatest extent.
[0014] Preferably, in S4, the concentration of the black phosphorus ethanol dispersion is 0.1-0.3 mg / mL, and the parameters for ice-water bath treatment are: treatment under 200-300W ultrasonic conditions for 2.5-3.5 h to obtain 3-5 layers of black phosphorus nanosheets loaded on electrode defect sites.
[0015] By utilizing the electrostatic adsorption and confined guidance effect of oxygen vacancies in the substrate, 3-5 layers of ultrathin black phosphorus nanosheets were obtained through in-situ exfoliation, and the black phosphorus nanosheets were precisely oriented and loaded onto the active sites of electrode defects, achieving precise matching of active sites.
[0016] Preferably, in step S4, the process involves constant-temperature curing at 50-60℃ under vacuum conditions ≤-0.08MPa for 1.5-2.5 hours to construct a stable Zr-OP covalent bond interface, replacing the weak interface effect of traditional physical bonding. Subsequently, the process is left to stand in a nitrogen-sealed, light-protected environment for 10-14 hours to complete the inert light-protected passivation stabilization treatment, which can slowly release residual stress at the interface and form an inert protective layer on the black phosphorus surface, effectively inhibiting the oxidation and deactivation of black phosphorus.
[0017] A black phosphorus zirconium-doped titanium suboxide electrode for removing perfluorinated contaminants is prepared using the above-described method for preparing a black phosphorus zirconium-doped titanium suboxide electrode for removing perfluorinated contaminants.
[0018] The prepared black phosphorus zirconium-doped titanium suboxide electrode uses zirconium defect-modified titanium suboxide as a substrate, with a surface rich in high-density stable oxygen vacancies. The ultrathin black phosphorus nanosheets are atomically tightly composited through Zr-OP covalent bonds, resulting in high interfacial bonding strength and low electron transport resistance. It combines the specific fluorine coordination adsorption capacity of zirconium-based materials with the fluorine-blocking characteristics of black phosphorus interfacial polarization, exhibiting abundant active sites and excellent stability.
[0019] This invention relates to a black phosphorus zirconium-doped titanium suboxide electrode for removing perfluorinated pollutants, applied to the electrochemical deep degradation of perfluorinated pollutants. The application method is as follows: using the black phosphorus zirconium-doped titanium suboxide electrode as the anode and a conventional titanium plate as the cathode, an electrochemical degradation system is constructed. Under normal temperature and pressure and a constant cell voltage of 2.5-4.0V, perfluorinated pollutants are electrochemically treated. Relying on the synergistic mechanism of selective enrichment-polarization bond breaking-electrochemical mineralization, the system achieves efficient defluorination and deep mineralization removal of trace and ultra-trace perfluorinated pollutants in water.
[0020] This invention pioneers an integrated fabrication process for zirconium defect pre-implantation coupled with in-situ bonding of black phosphorus, abandoning the traditional method of simple surface coating and physical composite modification of electrodes. By simultaneously chelating doped zirconium ions in a titanium-based system, atomic-level uniform dispersion of zirconium is achieved within the sub-titanium oxide lattice. Combined with a gradient oxygen-controlled sintering strategy, this effectively avoids problems such as grain coarsening, lattice defect annihilation, and segregation and agglomeration of active components caused by traditional high-temperature sintering. It stably constructs a high-density, highly reactive oxygen vacancy defect structure, optimizing the electrode lattice structure and electrochemical intrinsic properties at the substrate level, and providing sufficient active reaction sites for the adsorption, enrichment, and catalytic degradation of perfluorinated pollutants.
[0021] This invention utilizes the interfacial confinement-induced effect of substrate oxygen vacancies to achieve in-situ controllable exfoliation and directional loading of black phosphorus nanosheets, overcoming the technical bottlenecks of disordered nanosheet stacking, uneven layer count, and active site stacking failure in traditional black phosphorus composite processes. Simultaneously, through a vacuum eutectic curing process, a stable Zr-OP covalently bonded heterojunction is constructed between black phosphorus and a zirconium-modified titanium suboxide substrate, completely replacing the weak interfacial physical bonding of conventional electrodes. This significantly enhances the interfacial adhesion, effectively addressing the industry pain points of black phosphorus materials such as easy oxidation, easy detachment, and easy passivation and deactivation after long-term electrolysis, and significantly improving the overall structural stability and electron transport efficiency of the electrode.
[0022] Compared to conventional single-modified titanium suboxide electrodes, this invention innovatively integrates the dual advantages of zirconium-based fluorine coordination-specific adsorption and black phosphorus interfacial polarization-based fluoride breaking, constructing a novel synergistic degradation mechanism of selective enrichment-polarization bond breaking-electrochemical mineralization. The zirconium active sites can precisely capture trace amounts of perfluorinated pollutants in water, achieving targeted pollutant enrichment and avoiding ineffective electrolysis losses. The unique interfacial polarization effect of black phosphorus can efficiently weaken and break the highly stable carbon-fluorine bonds in perfluorinated pollutant molecules. Combined with the excellent electrochemical oxidation performance of the titanium suboxide substrate, this synergistic approach achieves deep defluorination and complete mineralization of perfluorinated pollutants, effectively overcoming the technical shortcomings of traditional modified electrodes, such as incomplete degradation of low-concentration perfluorinated pollutants, poor selectivity, and low mineralization.
[0023] Therefore, the present invention employs the above-mentioned black phosphorus zirconium-doped titanium suboxide electrode for removing perfluorinated contaminants and its preparation method, which has the following beneficial effects: (1) The preparation process adopted in this invention is simple, controllable, and highly repeatable. The entire process uses a green and low-toxicity solvent system, requiring no complex and precise equipment or harsh reaction conditions. The segmented preparation process is convenient to operate, suitable for large-scale processing and production, and has excellent industrial adaptability.
[0024] (2) The black phosphorus zirconium-doped titanium suboxide electrode prepared by the present invention has excellent electrochemical performance and engineering adaptability. The internal resistance of the electrode charge transfer can be as low as 12-18Ω, which is more than 35% lower than that of conventional single modified titanium suboxide electrodes, and the charge transport rate is significantly improved. Relying on the high-density oxygen vacancy and in-situ bonded composite structure of the substrate, the effective electrochemical active area of the electrode is greatly improved, which is 3-4 times that of the traditional surface-coated electrode, and can provide sufficient and accessible catalytic active sites.
[0025] (3) The black phosphorus zirconium sub-titanium oxide electrode prepared by the present invention has a wide range of water quality adaptability and can work stably in complex water environments with pH values of 4-10. The removal efficiency of trace PFOS pollutants in water is consistently maintained above 96%, which effectively solves the problems of poor acid and alkali adaptability and incomplete degradation of low-concentration pollutants of traditional electrodes.
[0026] (4) The black phosphorus zirconium sub-titanium oxide electrode prepared by the present invention can still maintain an initial PFOS removal rate of more than 94% after 12 consecutive cyclic electrolysis. The electrode interface structure is intact, with no obvious black phosphorus shedding or passivation of active sites. Its long-term operation stability is significantly better than that of traditional modified electrodes. It has extremely high application value and industrialization prospects in the fields of refined treatment of perfluorinated persistent organic pollutants and deep treatment of low-concentration complex PFOS wastewater.
[0027] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description
[0028] Figure 1 This is a graph showing the charge transfer internal resistance test results of the electrodes prepared in Examples 1-3 of the present invention for removing perfluorinated pollutants from black phosphorus zirconium-doped titanium suboxide and the preparation method thereof. Figure 2 This is a graph showing the charge transfer internal resistance comparison test results of the black phosphorus zirconium-doped titanium suboxide electrode for removing perfluorinated pollutants and the preparation method of the present invention, as well as the electrodes prepared by comparative examples 1-2. Figure 3 This is a graph showing the electrochemical active area test results of the electrodes prepared in Examples 1-3 of the present invention for removing perfluorinated pollutants from black phosphorus zirconium-doped titanium suboxide and its preparation method. Figure 4 This is a graph showing the electrochemical active area test results of the black phosphorus zirconium-doped titanium suboxide electrode for removing perfluorinated pollutants and the preparation method of the present invention, as well as the electrode prepared by Comparative Examples 1-2. Figure 5 This is a graph showing the degradation efficiency of PFOS on the electrodes prepared in Examples 1-3 of this invention for removing perfluorinated pollutants, specifically a black phosphorus zirconium-doped titanium suboxide electrode and its preparation method. Figure 6 This is a graph showing the degradation efficiency of PFOS on the black phosphorus zirconium-doped titanium suboxide electrode for removing perfluorinated pollutants and the preparation method of the present invention, as shown in Comparative Examples 1-2. Figure 7 This is a graph showing the removal efficiency of PFOS by the electrode prepared in Example 2 of the present invention for removing perfluorinated pollutants by zirconium-doped titanium suboxide under different pH conditions. Figure 8 This is a graph showing the PFOS removal efficiency of the electrode prepared in Example 2 of the present invention, which is a black phosphorus zirconium-doped titanium suboxide electrode for removing perfluorinated pollutants and its preparation method, during multiple cycles of use. Detailed Implementation
[0029] The technical solution of the present invention will be further described below with reference to the accompanying drawings and embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention should be considered equivalent substitutions and are included within the protection scope of the present invention. Furthermore, it should be understood that after reading the contents of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims and are all within the protection scope of the present invention.
[0030] In this document, the term "embodiment" means that a specific feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The term "embodiment" appearing in various places throughout the specification does not necessarily refer to the same embodiment, nor does it specifically limit its independence or connection with other embodiments. In principle, in this application, as long as there are no technical contradictions or conflicts, the technical features mentioned in each embodiment can be combined in any way to form corresponding implementable technical solutions.
[0031] Unless otherwise defined, the technical terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the use of related terms herein is merely for the purpose of describing particular embodiments and is not intended to limit this application.
[0032] In this invention, unless otherwise specified, all other test materials and instruments are conventional test materials in the field and can be purchased through commercial channels.
[0033] Example 1 This invention provides a method for preparing a black phosphorus zirconium-doped titanium suboxide electrode for removing perfluorinated contaminants, comprising the following steps: S1. Pretreatment of titanium plate substrate: High-purity titanium plate is selected as the substrate material. It is ultrasonically cleaned for 10 minutes each with acetone, anhydrous ethanol and ultrapure water to thoroughly remove oil, dust and oxide layer on the surface of the plate. Then it is placed in a 70℃ oven to dry fully and ready for use to obtain a clean and homogeneous titanium plate substrate.
[0034] S2. Preparation of zirconium-modified precursor sol: A homogeneous titanium-based alcoholysis system was constructed using tetrabutyl titanate as the titanium source, glacial acetic acid as the chelating agent, and anhydrous ethanol as the solvent. The mass ratio of the titanium source, chelating agent, and solvent was 1:2:5. Zirconium oxychloride was incorporated, with the zirconium element in the zirconium oxychloride doping mass fraction in the black phosphorus zirconium-doped titanium suboxide electrode being 1.0%. After continuous magnetic stirring for 40 min, the mixture was sealed and allowed to stand for 12 h to obtain a stable zirconium-modified precursor sol with uniform dispersion and no agglomeration or precipitation.
[0035] S3. Preparation of oxygen-rich vacancy zirconium-modified sub-titanium oxide substrate: The prepared zirconium-modified precursor sol was uniformly coated on the surface of the pretreated titanium plate substrate. After air drying at room temperature, it was transferred into a tube furnace. High-purity nitrogen was introduced throughout the process to maintain an inert protective atmosphere. The organic solvent was removed by first heating to 360℃ at 3℃ / min and holding for 30min. Then, the temperature was increased to 820℃ at 3℃ / min and sintered at a constant temperature for 2h to complete lattice reconstruction and defect construction. After that, the furnace was naturally cooled to room temperature to obtain the zirconium-modified sub-titanium oxide substrate electrode.
[0036] S4. In-situ bonding and passivation: A black phosphorus anhydrous ethanol dispersion with a concentration of 0.1 mg / mL was prepared. The zirconium-modified titanium suboxide substrate electrode prepared in S3 was immersed in the black phosphorus anhydrous ethanol dispersion and continuously sonicated for 2.5 h under ice-water bath and 200 W ultrasonic power. The black phosphorus was exfoliated and oriented by relying on the oxygen vacancy confinement effect of the substrate. Then, it was placed in a vacuum degree ≤ -0.08 MPa and light-proof environment at 50℃ for constant temperature curing for 1.5 h to build a stable Zr-OP covalent bonding interface. Finally, it was transferred to a nitrogen-sealed drying oven and placed in the dark for 10 h to complete the electrode passivation and stabilization treatment. The black phosphorus zirconium-doped titanium suboxide electrode was finally obtained, denoted as Zr-BP / Ti4O7-1 electrode.
[0037] Example 2 This invention provides a method for preparing a black phosphorus zirconium-doped titanium suboxide electrode for removing perfluorinated contaminants, comprising the following steps: S1. Titanium plate substrate pretreatment: High-purity titanium plate is selected as the substrate material. It is ultrasonically cleaned for 12 minutes each with acetone, anhydrous ethanol and ultrapure water to remove surface impurities and oxide layer. It is then dried in a 70℃ oven to obtain a clean and flat titanium plate substrate.
[0038] S2. Preparation of zirconium-modified precursor sol: A titanium-based alcoholysis system was constructed using tetrabutyl titanate as the titanium source, glacial acetic acid as the chelating agent, and anhydrous ethanol as the solvent. Zirconium oxychloride was incorporated, wherein the zirconium element in the zirconium oxychloride had a doping mass fraction of 2.0% in the black phosphorus zirconium-doped titanium suboxide electrode. After continuous magnetic stirring for 50 min, the system was sealed and allowed to stand for 18 h to prepare a zirconium-modified precursor sol with uniform composition and excellent stability.
[0039] S3. Preparation of oxygen-vacancy-rich zirconium-modified sub-titanium oxide substrate: The zirconium-modified precursor sol was uniformly coated on the surface of the titanium plate substrate, air-dried at room temperature, and then placed in a tube furnace with high-purity nitrogen gas. The temperature was first raised to 360℃ at 4℃ / min and held for 30min to remove solvent impurities. Then the temperature was raised to 840℃ at 3℃ / min and sintered at a constant temperature for 2.5h to promote the generation of high-density stable oxygen vacancies in the substrate. The substrate was then cooled to room temperature with the furnace to obtain the zirconium-modified sub-titanium oxide substrate electrode.
[0040] S4. In-situ bonding and passivation: A black phosphorus anhydrous ethanol dispersion with a concentration of 0.2 mg / mL was prepared. The zirconium-modified titanium suboxide substrate electrode prepared in S3 was immersed in the black phosphorus anhydrous ethanol dispersion and ultrasonically treated for 3 h under ice-water bath and 250 W ultrasonic power. The black phosphorus nanosheets were controllably exfoliated and precisely loaded by utilizing the substrate defect induction effect. The electrode was cured at a constant temperature of 55℃ under vacuum ≤ -0.08 MPa for 2 h to form a dense Zr-OP bonded heterojunction. The electrode was then passed through by standing in a nitrogen atmosphere in a dark place for 12 h to obtain a black phosphorus-doped zirconium-doped titanium suboxide electrode, denoted as Zr-BP / Ti4O7-2 electrode.
[0041] Example 3 This invention provides a method for preparing a black phosphorus zirconium-doped titanium suboxide electrode for removing perfluorinated contaminants, comprising the following steps: S1. Titanium plate substrate pretreatment: Select high-purity titanium plate as substrate, and ultrasonically clean it for 15 minutes each with acetone, anhydrous ethanol and ultrapure water to remove surface contaminants and oxide film. Place it in a 75℃ oven to dry for later use to ensure that the substrate surface is clean and free of impurities.
[0042] S2. Preparation of zirconium-modified precursor sol: A titanium-based chelate alcoholysis system was constructed using tetrabutyl titanate, glacial acetic acid, and anhydrous ethanol. Zirconium oxychloride was then incorporated, with the zirconium element in the zirconium oxychloride having a doping mass fraction of 3.0% in the black phosphorus zirconium-doped titanium suboxide electrode. After continuous magnetic stirring for 60 min, the mixture was sealed and aged for 24 h to obtain a zirconium-modified precursor sol with highly uniform composition and no particle agglomeration.
[0043] S3. Preparation of oxygen-vacancy-enriched zirconium-modified sub-titanium oxide substrate: The precursor sol was uniformly coated on the surface of the titanium plate, and after natural air drying, it was placed in a nitrogen-protected tube furnace; the temperature was first raised to 370℃ at 5℃ / min and held for 35min to completely remove the solvent, and then the temperature was raised to 860℃ at 4℃ / min and sintered at a constant temperature for 3h to accurately construct a stable oxygen vacancy defect structure. The furnace was then cooled to room temperature to obtain the zirconium-modified sub-titanium oxide substrate electrode.
[0044] S4. In-situ bonding and passivation: A black phosphorus anhydrous ethanol dispersion with a concentration of 0.3 mg / mL was prepared. The zirconium-modified titanium suboxide substrate electrode prepared in S3 was immersed in the black phosphorus anhydrous ethanol dispersion and treated under ice-water bath and 300W ultrasonic power for 3.5 h to achieve in-situ controllable exfoliation of black phosphorus multilayer nanosheets and directional loading of defect sites. It was cured for 2.5 h under vacuum degree ≤ -0.08 MPa and light-proof 60℃ to construct a high-strength Zr-OP covalent bonding interface. Passivation and stabilization were completed by nitrogen gas in a light-proof and sealed environment for 14 h to obtain the black phosphorus zirconium-doped titanium suboxide electrode, denoted as Zr-BP / Ti4O7-3 electrode.
[0045] Comparative Example 1 This comparative example provides a method for preparing a single zirconium-modified titanium suboxide electrode, including the following preparation steps: S1. Titanium plate substrate pretreatment: Select a high-purity titanium plate and ultrasonically clean it for 12 minutes each with acetone, anhydrous ethanol and ultrapure water, and dry it at 70°C to obtain a clean titanium plate substrate.
[0046] S2. Preparation of zirconium-modified precursor sol: According to the raw material ratio and process parameters of Example 2, prepare zirconium-modified precursor sol with a zirconium element mass fraction of 2.0%, stir for 50 min, and age in a sealed container for 18 h for later use.
[0047] S3. Preparation of zirconium-modified titanium suboxide electrode: The precursor sol was coated on the surface of the titanium plate and air-dried. The zirconium-modified titanium suboxide substrate was prepared by a segmented gradient sintering process that was completely consistent with that in Example 2. There was no black phosphorus loading or vacuum bonding passivation process throughout the process. Finally, a single zirconium-modified titanium suboxide electrode was obtained, which was denoted as Zr / Ti4O7-C1 electrode.
[0048] Comparative Example 2 This comparative example provides a conventional physical blending method for preparing a black phosphorus composite titanium suboxide electrode, including the following preparation steps: S1. Titanium plate substrate pretreatment: Select high-purity titanium plates, and clean and dry them with acetone, anhydrous ethanol, and ultrapure water to obtain a clean electrode substrate.
[0049] S2. Preparation of pure titanium suboxide substrate: Using the same sintering process as in Example 2, the pure titanium plate was subjected to high-temperature sintering treatment to prepare a pure titanium suboxide substrate electrode without zirconium modification and without defect control.
[0050] S3. Preparation of composite electrode by physical loading of black phosphorus: Using the same concentration of black phosphorus dispersion as in Example 2, the black phosphorus dispersion was applied to the surface of pure titanium suboxide substrate by conventional direct drop coating. After natural air drying, without vacuum bonding or inert passivation treatment, black phosphorus loading was achieved solely by physical adsorption, thus obtaining a traditional physical composite black phosphorus titanium suboxide electrode, denoted as BP / Ti4O7-C2 electrode.
[0051] The electrodes prepared in Examples 1-3 and Comparative Examples 1-2 were systematically characterized for electrochemical performance and PFOS degradation performance. All tests were conducted under normal temperature and pressure conditions, with a single variable controlled throughout to ensure the accuracy, reliability, and comparability of the test data. The specific test methods and experimental results are as follows: (1) Electrochemical impedance performance test of electrodes: Electrochemical impedance spectroscopy (EIS) performance was tested using a standard three-electrode system. The base electrolyte was a 0.5 mol / L neutral sodium sulfate solution. The modified electrode under test was used as the working electrode, a high-purity platinum sheet as the counter electrode, and a saturated calomel electrode as the reference electrode. The EIS test frequency range was set to 0.01 Hz–100 kHz, with a small AC excitation signal of 5 mV. The interfacial charge transfer resistance of each electrode was analyzed by equivalent circuit fitting to evaluate the electrode's electronic conductivity.
[0052] Test results are as follows Figures 1-2 As shown, by Figure 1 It can be seen that the charge transfer internal resistance of the Zr-BP / Ti4O7-1 electrode prepared in Example 1 is 16.5Ω, the internal resistance of the Zr-BP / Ti4O7-2 electrode prepared in Example 2 is as low as 13.2Ω, and the internal resistance of the Zr-BP / Ti4O7-3 electrode prepared in Example 3 is 15.8Ω. Figure 2 It can be seen that the internal resistance of the single zirconium-modified electrode in Comparative Example 1 is 28.6Ω, and the internal resistance of the traditional physical composite black phosphorus electrode in Comparative Example 2 is 24.3Ω. The internal resistance of the electrodes in each embodiment is significantly lower than that of the comparative example electrodes, proving that the zirconium defect pre-construction coupled Zr-OP covalent bonding process of the present invention can effectively optimize the electrode interface structure, reduce the charge transport barrier, and significantly improve the electron conduction efficiency.
[0053] (2) Effective electrochemical active area test: The effective electrochemical active area of each electrode was characterized using the double-layer capacitance method. In a 0.5 mol / L sodium sulfate electrolyte system, a constant potential window of 0.1 V–0.3 V was set, and cyclic voltammetry tests were performed at scan rates of 10 mV / s, 20 mV / s, 40 mV / s, 60 mV / s, 80 mV / s, and 100 mV / s. Instantaneous current data at a potential of 0.2 V were collected, and the double-layer capacitance was obtained by linearly fitting the scan rate and the current density. The slope of the fitting was the double-layer capacitance value, which was positively correlated with the electrochemical active area of the electrode.
[0054] Test results are as follows Figures 3-4 As shown, by Figure 3 It can be seen that the double-layer capacitance values of the electrodes in Examples 1, 2, and 3 are 2.56 mF / cm. 2 2.89mF / cm 2 2.71mF / cm 2 .Depend on Figure 4 It can be seen that the double-layer capacitance of the electrodes in Comparative Example 1 and Comparative Example 2 is only 1.03 mF / cm. 2 1.42mF / cm 2 Compared to Comparative Examples 1-2, the composite electrodes prepared in Examples 1-3 showed a significantly increased active reaction interface. This was due to the synergistic effect of oxygen vacancy defect sites and in-situ bonded black phosphorus nanosheets, which effectively solved the problems of low number and low exposure of active sites in traditional modified electrodes.
[0055] (3) PFOS electrochemical degradation performance test: The electrochemical degradation performance of PFOS was tested in a 300 mL open glass reactor. The experimental system used the electrode under test as the anode and a titanium plate of equal area as the cathode, with a fixed electrode spacing of 2 cm. Simulated wastewater containing 10 mg / L PFOS was prepared, with 0.05 mol / L sodium sulfate added as a supporting electrolyte; no additional chemical oxidant was required. A constant cell voltage of 2.8 V was applied during the experiment, and electrolysis was performed continuously for 4 hours. Samples were taken every 1 hour. After filtration through a 0.22 μm organic filter membrane, the residual PFOS concentration in the water was measured using liquid chromatography-mass spectrometry (LC-MS / MS), and the pollutant degradation and removal rate was calculated based on the concentration difference.
[0056] Test results are as follows Figures 5-6 As shown, by Figure 5 It can be seen that the PFOS degradation and removal rates of Examples 1, 2, and 3 can reach 98.3%, 99.8%, and 97.9%, respectively. Figure 6It can be seen that the removal rate of the single zirconium-modified electrode in Comparative Example 1 is only 71.6%, while the removal rate of the traditional physical composite electrode in Comparative Example 2 is 80.2%. It is evident that the zirconium-based enrichment-black phosphorus bond-breaking synergistic system constructed in this invention can efficiently break the carbon-fluorine bonds of PFOS, thereby achieving deep mineralization removal of recalcitrant perfluorinated pollutants.
[0057] (4) Water quality acidity and alkalinity compatibility test: To verify the water quality acidity and alkalinity adaptability of the electrode, the composite electrode of Example 2 with the best performance was selected to conduct a wide pH adaptability experiment, such as... Figure 7 As shown in the figure. The pH values of the simulated PFOS wastewater were adjusted to 4, 6, 7, 9, and 10, respectively, while the other electrolysis process parameters remained the same. After continuous reaction for 4 hours, the PFOS removal effect of each group was detected.
[0058] Experimental data show that under the different acid and alkaline conditions, the PFOS removal rates of the electrode were 97.8%, 98.8%, 99.8%, 98.2%, and 97.6%, respectively, with the removal efficiency remaining stable above 96% across the entire range, without significant performance degradation. Compared to the drawback of conventional titanium suboxide electrodes, which exhibit a sharp drop in activity in alkaline environments, the composite electrode of this invention possesses excellent wide pH tolerance and can be adapted to PFOS wastewater treatment scenarios with complex acid and alkaline water qualities.
[0059] (5) Cyclic service stability test: The cyclic stability of the electrode was evaluated through multi-cycle continuous electrolysis experiments. Using the composite electrode prepared in Example 2 as the research object, 12 sets of cyclic electrolysis tests were continuously completed under standard degradation experimental conditions. Each set of electrolysis lasted 4 hours. After each experiment, the electrode surface was thoroughly rinsed with ultrapure water, and the electrode was replaced with fresh simulated wastewater before the next round of testing. The PFOS degradation efficiency for each cycle was statistically analyzed. The test results are as follows: Figure 8 As shown, the removal rate was 99.8% in the first cycle, 98.4% in the sixth cycle, and still maintained a high removal rate of 94.9% in the twelfth cycle. The electrode activity decay rate was slow, with no obvious site passivation or coating peeling, and it has excellent reusability.
[0060] Based on the above test results, the composite electrode prepared by the present invention through zirconium defect modification coupled with black phosphorus in-situ bonding process is superior to single modified electrodes and traditional physical composite electrodes in terms of core performance such as electron conduction rate, effective catalytic active area, PFOS deep degradation ability, water quality adaptability, cycle stability and long service life. It effectively breaks through the technical bottleneck of existing titanium suboxide modified electrodes for treating perfluorinated pollutants.
[0061] Therefore, this invention employs the aforementioned black phosphorus zirconium-doped titanium suboxide electrode for removing perfluorinated pollutants and its preparation method. Relying on the synergistic effect of zirconium-based fluorine coordination enrichment and black phosphorus interface polarization bond breaking, a novel perfluorinated pollutant degradation mechanism is constructed. This mechanism efficiently breaks highly stable carbon-fluorine bonds, resulting in an electrode with low internal resistance, high utilization of active sites, and excellent anti-interference and cycling stability. It can achieve deep defluorination and mineralization of trace perfluorinated pollutants in complex water bodies. The process is simple, controllable, and highly reproducible, possessing good engineering application and industrialization prospects.
[0062] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the technical solutions of the present invention, and these modifications or equivalent substitutions cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.
Claims
1. A method for preparing a black phosphorus zirconium-doped titanium suboxide electrode for removing perfluorinated contaminants, characterized in that: Includes the following steps: S1. Titanium plate substrate pretreatment: High-purity titanium plates are treated with organic solvents combined with ultrasonic cleaning and drying to remove surface oil and oxidation impurities and obtain a clean titanium plate substrate. S2. Preparation of zirconium-modified precursor sol: Zirconium oxychloride single precursor is incorporated into a titanium-based alcoholysis system, and after thorough stirring and sealed aging, zirconium-modified precursor sol is obtained. S3. Preparation of oxygen-vacancy-rich zirconium-modified sub-titanium oxide substrate: The zirconium-modified precursor sol obtained in S2 is uniformly coated on the surface of the titanium plate substrate obtained in S1, and processed by a segmented gradient oxygen-controlled sintering process under a nitrogen atmosphere to obtain a zirconium-modified sub-titanium oxide substrate electrode rich in stable oxygen vacancy defects. S4. In-situ bonding and passivation: Prepare a black phosphorus ethanol dispersion, immerse the zirconium-modified titanium suboxide substrate electrode prepared in S3 into the black phosphorus ethanol dispersion, and perform ice-water bath treatment. Then, construct the Zr-OP covalent bonding interface by vacuum eutectic solidification. Finally, passivate the electrode with inert light-shielding to obtain the black phosphorus zirconium-doped titanium suboxide electrode.
2. The method for preparing a black phosphorus zirconium-doped titanium suboxide electrode for removing perfluorinated contaminants according to claim 1, characterized in that: The specific operation of S1 is as follows: the high-purity titanium plate is ultrasonically cleaned with acetone, anhydrous ethanol and ultrapure water for 10-15 minutes respectively, and then dried in an oven at 60-80℃ for later use.
3. The method for preparing a black phosphorus zirconium-doped titanium suboxide electrode for removing perfluorinated contaminants according to claim 1, characterized in that: In S2, the titanium-based alcoholysis system consists of a titanium source, a chelating agent, and a solvent. The titanium source is tetrabutyl titanate, the chelating agent is glacial acetic acid, and the solvent is anhydrous ethanol. The zirconium element in zirconium oxychloride has a doping mass fraction of 1-3% in the black phosphorus zirconium-doped titanium suboxide electrode. The stirring time is 40-60 min, and the sealed aging time is 12-24 h.
4. The method for preparing a black phosphorus zirconium-doped titanium suboxide electrode for removing perfluorinated contaminants according to claim 3, characterized in that: In S2, the mass ratio of titanium source, chelating agent, and solvent is 1:(1-3):
5.
5. The method for preparing a black phosphorus zirconium-doped titanium suboxide electrode for removing perfluorinated contaminants according to claim 1, characterized in that: In S3, the segmented gradient oxygen-controlled sintering process is as follows: high-purity nitrogen gas is continuously introduced for protection. First, the temperature is raised to 350-380℃ at 3-5℃ / min and held for 25-35min to remove the solvent. Then, the temperature is raised to 820-860℃ at 3-4℃ / min and sintered at a constant temperature for 2-3h. The furnace is then allowed to cool naturally.
6. The method for preparing a black phosphorus zirconium-doped titanium suboxide electrode for removing perfluorinated contaminants according to claim 1, characterized in that: In S4, the concentration of black phosphorus ethanol dispersion is 0.1-0.3 mg / mL, and the parameters for ice-water bath treatment are: treatment under 200-300W ultrasonic conditions for 2.5-3.5 h to obtain 3-5 layers of black phosphorus nanosheets loaded on electrode defect sites.
7. The method for preparing a black phosphorus zirconium-doped titanium suboxide electrode for removing perfluorinated contaminants according to claim 1, characterized in that: In S4, a stable Zr-OP covalent bonding interface is constructed by constant temperature curing for 1.5-2.5 hours under vacuum conditions ≤-0.08MPa and light-proof conditions at 50-60℃. Subsequently, the mixture is left to stand in a nitrogen-sealed, light-proof environment for 10-14 hours to complete the inert light-proof passivation stabilization treatment.
8. A black phosphorus-doped zirconium sub-titanium oxide electrode for removing perfluorinated contaminants, characterized in that: The black phosphorus zirconium-doped titanium suboxide electrode for removing perfluorinated contaminants was prepared using the method described in any one of claims 1-7.